Antimicrobial synergism against different lineages of methicillin-resistant Staphylococcus aureus carrying SCCmec IV - Matos, Pricilla D. M. de (2014)
Aim To evaluate the synergistic activity of antimicrobial drugs against lineages of methicillin-resistant Staphylococcus aureus (MRSA) carrying SCCmec IV. The biofilm production and related genes were also detected. Methods and Results Forty two MRSA isolates were tested for biofilm production and related genes. Biofilm/biomass susceptibility to gentamicin (G), linezolid (L), rifampicin (R) and vancomycin (V) was determined for six isolates from three lineages prevalent in Rio de Janeiro hospitals in concentrations ranging from 0·25 to 64 μg ml−1. Biomass was evaluated by microtitre plate test and number of viable cells (CFU cm−2) and inspected by epifluorescence microscopy. All isolates presented the icaA and sasG genes, but only 38% were biofilm producers. There were 50 and 45% biomass reductions when concentrations ≥4 μg ml−1 of R or L and ≥16 μg ml−1 of G or V, respectively, were used. Synergism tests produced a 55% biomass reduction with R2lg ml1 + G16lg ml1 , R2lg ml1 + L2lg ml1 , R2lg ml1 + V4lg ml1 , and L2lg ml1 + V4lg ml1 . Number of viable cells was reduced from 2 to 3 logs with R2lg ml1 + L2lg ml1 and R2lg ml1 + V4lg ml1 . Conclusions Synergisms involving R plus L and R plus V caused important reductions in biofilm/biomass and the number of viable cells. Drug combinations should be considered in the chemotherapies of MRSA-SCCmec IV infections. Significance and Impact of the Study Biofilms in MRSA infections restrict the clinical choice of antimicrobials. Thus, knowledge of the best options for monotherapy and drug synergisms could improve clinical results.